ANALISIS FAKTOR YANG MEMPENGARUHI LUAS PENGUNGKAPAN SOSIAL DAN LINGKUNGAN MELALUI WEBSITE PERUSAHAAN - Nuzul Noor Ramadhan; Andri Prastiwi (Diponegoro Journal of Accounting, 2014)
The purpose of this research is to analyze factors namely corporate type, profitability, foreign ownership, firm size, and corporate age that influence the extent of corporate social and environmental disclosure through corporate website. This research was made to continue previous research which focused only on the extent of corporate social dan environmental disclosure.            The statistic method that used to test the hypothesis in this research is multiple regression analysis. The population in this research is whole firm that listed on Indonesian Stock Exchange in 2011 until 2012. Sampling method used was random sampling. The final amount of sample are 60 firm.            Result of multiple regression analysis shows that corporate type, firm size, and corporate age have significant positive effect on the extent of corporate social and environmental disclosure through corporate website. Meanwhile, the other two variable that is profitability and foreign ownership have no significant effect on the extent of corporate social and environmental disclosure through corporate website.